(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This empirical study investigates the prevalence and impact of overconfidence bias among 150 women investors across India, a demographic often underrepresented in behavioral finance research. Overconfidence bias refers to an investor’s tendency to overestimate their knowledge and decision-making abilities, which can result in impulsive or risky financial behaviors. Through a structured quantitative design employing surveys and statistical analysis using Smart PLS, the study identifies a significant positive relationship between overconfidence and investment decisions. Notably, women investors with higher levels of financial literacy demonstrated lower susceptibility to overconfidence bias, highlighting the critical moderating role of financial knowledge. The analysis further revealed that women with higher income levels exhibited greater overconfidence, underscoring the influence of demographic factors. These findings emphasize the necessity for targeted financial literacy programs that not only impart knowledge but also address cognitive and psychological dimensions of investing. By focusing on the behavioral tendencies of women investors, the study contributes to a more inclusive understanding of financial decision-making in the Indian context. The results aim to guide policymakers, financial institutions, and educators in designing interventions that empower women to make informed and confident investment choices while mitigating the risks posed by behavioral biases.